Family crisis and its relationship with self-motivation among secondary school students (Journal of the College of Basic Education, 2019)
The current research aims at identifying the family crisis and the self-motivation of the preparatory students according to the specialization variable (scientific, literary) and the relationship between them. The current research sample consisted of 200 students. After the two measures were built and applied to the sample, the data were analyzed using appropriate statistical means to address them , The results of the study showed that individuals suffering from the family crisis enjoy low self motivation, and that the students of the scientific branch suffer from the impact of the family crisis more than the students of the literary branch, and the researcher reached a number of recommendations and suggestions